Rewards and Drawbacks of Flexible Learning: The Case of Students in Public Higher Education Institution - Carillo, Franklin John; Maganding, Monnien; San Jose, Ariel (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
College students in rural areas in the Philippines were used to the traditional learning approach. The Flexible Learning (FL) though sounds enticing and inviting, was new and foreign to them.  This qualitative-phenomenological study explored the individual experiences, perspectives, and views of college students on Flexible Learning (FL) during the COVID 19. Using the non-probability sampling, the researchers purposely chosen 24 college students. The researchers used a validated and structured interview guide to obtain the data. Findings revealed that Flexible Learning offered autonomy, more family time, and entrepreneurial opportunities. However, the transition from traditional to Flexible Learning (FL) triggered much anxiety especially to those who experienced low internet access, no gadgets, unresponsive mentors, and living in far flung areas. Despite the drawbacks, students remained resilient, positive, and developed adaptive behaviors. The results imply that Higher Educational Institutions (HEIs) may look into the institution’s technological capacity, students’ needs, and academic readiness before deciding to implementing Flexible Learning (FL) so that it can serve better the students.